Presentación de servicios en casos nuevos de pacientes con tuberculosis pulmonar con bacilo de Koch positivo BK+ en la zona siete Ecuador. - Clemente Mestanza, Griselda Saria (2014)
The present investigation on " Provision of services in patients' new cases with pulmonary tuberculosis with bacillus of Koch positive (bk +) in the zone seven - equator "forms a part of the general project" bacteriological Conversion associated with co-morbidity, provision of services and patients' attitude, in new cases of Pulmonary Tuberculosis BK +. Zone 7. Ecuador “, that is executing the Program of Investigation and Epidemiology of Loja's National University. The type of study is descriptive with a duration of 12 months. The Universe the new Cases constitute with diagnosis of pulmonary Tuberculosis BK + that receive treatment antifímico during the period of investigation in the units of health of the MSP of the Zone Seven, for the compilation of the information there was in use the technology of the structured interview, as well as form of beginning and follow-up. The obtained results demonstrate that 91 % of the new cases with diagnosis of tuberculosis BK +, the administration of the medicines is given on the part of the personnel of health, 96 % of the patients who receive the treatment is directly observed; and 83 % of the new cases with diagnosis of pulmonary Tb BK + is present to receive the treatment, being demonstrated that in an average of 90 %, the strategy DOTS recommended by the Pan-American Organization of the Health (OPS) in the Ecuador from the year 2001 is being applied in agreement to the established.